1997
DOI: 10.1037/1076-8998.2.4.289
|View full text |Cite
|
Sign up to set email alerts
|

Work characteristics and employee well-being within a context of strategic downsizing.

Abstract: Findings from this 4-year longitudinal study of strategic downsizing suggest that introducing deliberate work organization and change management strategies can combat the negative effects of reduced head count. Results showed that there was no overall decrease in well-being from before to after downsizing for the 139 employees remaining in an organization, despite an increase in work demands. The potentiai detrimental effect of demands appears to have been offset by improvement in work characteristics arising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
136
1
7

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(152 citation statements)
references
References 36 publications
8
136
1
7
Order By: Relevance
“…(Park et al, 2004) An uncontrolled UK study found improvements in mental health (mean anxiety and depression scores) amongst manual workers (from 2.71 to 2.45; p<0.01) but not managers or clerical employees. (Parker et al, 1997) This review met all of the appraisal criteria.…”
Section: Employee Controlmentioning
confidence: 99%
“…(Park et al, 2004) An uncontrolled UK study found improvements in mental health (mean anxiety and depression scores) amongst manual workers (from 2.71 to 2.45; p<0.01) but not managers or clerical employees. (Parker et al, 1997) This review met all of the appraisal criteria.…”
Section: Employee Controlmentioning
confidence: 99%
“…However, they have not employed the rigorous, statistical procedures (see Barnett et al, 1999;Baron & Kenny, 1986; Holmbeck, 1997;Kenny, 1998) that are needed to assess whether or not any such relationships result from job control mediating stress-related outcomes. For example, the association between increased control and well-being that Parker et al (1997) noted may have occurred for one of two reasons.…”
Section: Job Control Stress-related Outcomes and Work Reorganizatiomentioning
confidence: 99%
“…There have, however, certainly been work reorganization outcome studies that have tested for relationships between improvements in job control and stress-related outcomes. For example, Parker, Chmiel, and Wall (1997) found a significant relationship between increases in control and job satisfaction, four years after a chemical processing plant instituted strategic downsizing in association with an "empowerment initiative". In contrast, Jackson and Martin (1996) found that changes in timing control (i.e., control over work scheduling) were not associated with changes in psychological strain or job satisfaction, seven months after a manufacturing plant instituted a just-in-time production system.…”
Section: Job Control Stress-related Outcomes and Work Reorganizatiomentioning
confidence: 99%
See 1 more Smart Citation
“…support to employees is a powerful tool for organization to attenuate negative effects of downsizing and contract breaches (Brockner et al, 2004;Dulac, Coyle-Shapiro, Henderson, & Wayne, 2008;Parker et al, 1997). It is therefore important to investigate whether support from the manager can be a buffer for employees against negative effects of mass layoffs.…”
mentioning
confidence: 99%